FACTORS AFFECTING EARNING MANAGEMENT IN MANUFACTURING COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Anita Rakhmawati; Magda Siahaan; Bonar Paul Siahaan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
The aim of this study is to gather empirical data on how factors like growth, company size, return on assets, debt ratio, size of audit firm, presence of an independent board of commissioners, and the size of the board of directors impact earnings management in the Indonesian stock market.   The research focused on manufacturing companies listed on the Indonesia Stock Exchange between 2017 and 2019. By using a purposive sampling technique and identifying 73 qualifying companies, the study conducted data analysis through multiple regression. The findings indicate that return on assets plays a significant role in influencing earnings management. Conversely, factors such as company growth, size, debt ratio, audit firm size, presence of an independent board of commissioners, and board size do not have a discernible impact on earnings management practices within the companies.